Madness, Power and the Media - Harper, S. author. aut Link
VI, 238 p.
Keywords: Questioning the psychiatric construction of mental distress as 'illness', and challenging existing studies of media stigmatization, Stephen Harper argues that today's media images of mental distress are often sympathetic, yet tend to reproduce the sexist, classist, racist and individualist ideologies of contemporary capitalism.